2003
DOI: 10.1038/sj.bmt.1703884
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Helicobacter pylori on platelets after bone marrow transplantation from unrelated donors

Abstract: Summary:This study was performed to clarify the influence of Helicobacter pylori on the platelet count in patients undergoing bone marrow transplantation (BMT) from unrelated donors. Of 23 consecutive patients undergoing BMT from unrelated donors, the H. pylori antibody test did not change from before conditioning until recovery of the platelet count in 15 patients. These patients were classified into H. pylori antibody-positive (n ¼ 8) and -negative (n ¼ 7) groups. In the H. pylori antibody-positive group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(16 reference statements)
0
3
1
Order By: Relevance
“…However, in a study of Chinese carriers of H. pylori during allogeneic bone marrow transplantation, a positive association between H. pylori carriage and reduced risk of gut acute GVHD was demonstrated 1 . Although a previous study has shown that H. pylori infection accelerates recovery of the platelet count after HSCT, possibly by stimulating IL-6 production 20 , we have not identified any association between platelet, leukocyte and neutrophil counts and the presence of H. pylori in the oral mucosa.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…However, in a study of Chinese carriers of H. pylori during allogeneic bone marrow transplantation, a positive association between H. pylori carriage and reduced risk of gut acute GVHD was demonstrated 1 . Although a previous study has shown that H. pylori infection accelerates recovery of the platelet count after HSCT, possibly by stimulating IL-6 production 20 , we have not identified any association between platelet, leukocyte and neutrophil counts and the presence of H. pylori in the oral mucosa.…”
Section: Discussioncontrasting
confidence: 41%
“…In addition, as a recent study demonstrated a reduced incidence of acute GVHD of the gut in Chinese carriers of H. pylori during allogeneic bone transplantation 1 , we studied the effect of the presence of H. pylori on the severity of oral GVHD. Finally, as H. pylori has an influence on the platelet count in HSCT patients 20 , the association between platelets number and the presence of H. pylori was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Can pathogens present in one strain, but absent in another, bias published conclusions on the role of a specific receptor or ligand? To date, no information is available, but it is worth acknowledging the studies on another Helicobacter species, Helicobacter pylori, and a growing awareness for its ability to influence aspects of platelet function (62,63).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the effect of H. pylori infection on platelets, Wakae et al reported rapid recovery in peripheral platelet counts after the bone marrow transplantation among H. pylori-positive patients. Platelet counts of H. pylori-positive patients reached 20 Â 10 9 /l 16.4þ/À2.7 days after bone marrow transplantation, whereas the negative patients required 32.4þ/À13.3 days [11]. Recently, Ozel et al reported lower levels of IL-6 in H. pylori-negative patients and its decline after eradication of H. pylori in patients with Familial Mediterranean Fever [12].…”
Section: Discussionmentioning
confidence: 96%